Flow and Manufacturing Variation of Drippers - Singh, Atul Kumar; Upadhyaya, A; Islam, A; Bharali, M A; Roy, Manoj (Journal of Agricultural Engineering, 2006)
Uniformity includes two key elements describing how well the emission device is designed and how well it is manufactured. These two elements are known as the flow exponent "x" and the coefficient of manufacturing variation, "CV". Both these "x" and the "CV" are integral parts of the Emission Uniformity equation, which describes uniformity due to manufacturing design and variation. The flow exponent x describes how "pressure compensating" the emission device is, and normally measures between 0 to 1, the lower (closer to 0) the value of x, the better (pressure compensating), values of 0.5 represent turbulent flow and values of 1.0 represent laminar flow. While CV is a statistical description of how uniformly each device is manufactured in relation to one another in terms of its flow rate. The paper presents the values of x and CV estimated through laboratory test of emitters used commercially in India belonging to some of the leading manufacturers. It was observed that none of the emitters could be termed as pressure compensating while values of CV for most of the emitters ranges between 0.1-0.25.